2013
DOI: 10.3351/ppp.0007.0001.0004
|View full text |Cite
|
Sign up to set email alerts
|

Homelessness and identity: a critical review of the literature and theory

Abstract: Within the news media and literature, alike, people experiencing homelessness are often categorised into various stereotypes revolving around their lack of abode. In such a practice a 'homeless identity' becomes the defining feature of a person's character. Very few theoretical studies have critically addressed this discursive construction and its implications. This paper contributes to the few existing debates around the 'homeless identity' by arguing that such constructions are binding and misguided. The pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 35 publications
2
30
0
1
Order By: Relevance
“…In accordance with the Behavioral Model for Vulnerable Populations, our participants live like others with severe disability in a culture of poverty, stigma and victimization . They experience difficulties appraising and coping with street‐life, which influences the availability, affordability and ultimately the accessibility of healthcare including dentistry.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In accordance with the Behavioral Model for Vulnerable Populations, our participants live like others with severe disability in a culture of poverty, stigma and victimization . They experience difficulties appraising and coping with street‐life, which influences the availability, affordability and ultimately the accessibility of healthcare including dentistry.…”
Section: Discussionmentioning
confidence: 90%
“…Homelessness is a chronic condition that disturbs personal identity through violence, oppression, victimization and stigma . It can also disrupt how people appraise and cope emotionally with illness, which, according to Lazarus's Theory of Emotions, is a cognitive, motivational and relational process of personal adaptation to stress .…”
Section: Introductionmentioning
confidence: 99%
“…social interaction under the impact of the symptoms' and so 'attention to bodily states are not brought into consciousness'? (22) Homelessness is a dynamic process (23), with multiple pathways in and out of homelessness, a multitude of homelessness experiences, and a variety of ways that individuals negotiate their way around and through their homelessness journeys. Coles' (24) qualitative exploration of homelessness found that homelessness journeys were underpinned by a trajectory, which defined people's expeditions into, through and out of homelessness.…”
mentioning
confidence: 99%
“…Goffman's (1959) impression management is where social actors present versions of their identity depending on the context of their interaction (Goffman, 1959). Identity is a performance, with social actors performing a particular role to a set of observers (McCarthy, 2013: Goffman, 1959. The "expressive equipment" that is consciously or unconsciously used in these performances was termed a front by Goffman (Goffman, 1959: 32).…”
Section: Theorising Identitymentioning
confidence: 99%